Minimally invasive pancreaticoduodenectomy for periampullary disease: it’s time for a randomized control trial! - Esposito, Alessandro; De Pastena, Matteo; Salvia, Roberto (Laparoscopic Surgery, 2018)
During the 1980’s, the introduction of laparoscopy as support to abdominal surgery changed in a revolutionary and innovative way the thoughts and the habits of the surgeons.